CONSUMER'S ORIENTED DENTAL SERVICE QUALITY ASSESSMENT USING THE SERVQUAL MODEL - Zaura Anggraeni; Emmy Hastuti; Felix Aryadi (Faculty of Dentistry, Universitas Indonesia, 2015)
Consumers oriented quality in dental health services has become more important in the era of free competition. Perceived quality by the community has been closely related with their previous experience level of satisfaction on the quality of services they received. The information on the perceived quality of dental services in Indonesia has been scarce. One of the reasons is lack of standardized method in measuring the consumer's perspective on dental quality. Using the Service Quality (Servqual) model cross-sectionally, this study is to investigate differences in patterns on perceived quality of different groups of Puskesmas (government owned) and Syahid clinic (private owner) consumers. The analysis of Servqual Kartesius diagram was carried out to assess the quality of service, based on various criteria namely Dimesntions of Physical Tangibles, Reliability, Responsiveness, Assurance and Empathy. Results showed differences in quality perception likely due to differences in level of education and income. It was concluded that the Servqual model has been adequately practical for assessing quality dental services based on level of consumer's satisfaction and degree of importance as measured from the consumer's perspective. Eventuallym the results of Servqual measurements can be used as guidance for quality improvements of dental services, based different characteristics of consumers.